The composition of certain lipids in man : a comparative study of lipids in total serum, in the serum B-lipoprotein fraction and in arterial atheromatous plaques in certain groups of people - Young, Gerardine Olga (Division of Human Nutrition, 2020)
In recent years biochemical studies have played an important role in research into the pathogenesis of ischaemic heart disease. A large number of these studies have been concerned with the relationship between serum lipids and ischaemic heart disease (I.H.D.), which has been defined by the World Health Organization (1957) as "the cardiac disability, acute and chronic, arising from reduction or arrest of blood supply to the myocardium in association with disease processes in the coronary arterial system".